Tripartite Motif-Containing Protein 22 Interacts with Class II Transactivator and Orchestrates Its Recruitment in Nuclear Bodies Containing TRIM19/PML and Cyclin T1 - Forlani, Greta; Tosi, Giovanna; Turrini, Filippo; Poli, Guido; Vicenzi, Elisa; Accolla, Roberto S. (Frontiers in Immunology, 2017)
Among interferon (IFN) inducible antiviral factors both Tripartite motif-containing protein 22 (TRIM22) and Class II Transactivator (CIITA) share the capacity of repressing HIV-1 proviral transcription. TRIM22 is constitutively expressed in a subset of U937 cell clones poorly permissive to HIV-1 replication, whereas CIITA has been shown to inhibit virus multiplication in both T lymphocytic and myeloid cells, including poorly HIV-1 permissive U937 cells, by suppressing Tat-mediated transactivation of HIV-1 transcription. Therefore, we tested whether TRIM22 and CIITA could form a nuclear complex potentially endowed with HIV-1 repressive functions. Indeed, we observed that TRIM22, independently of its E3-ubiquitin-ligase domain, interacts with CIITA and promotes its recruitments it into nuclear bodies. Importantly, TRIM19/Promyelocytic Leukemia (PML) protein, another repressor of HIV-1 transcription also acting before proviral integration, was observed to colocalized in these nuclear bodies upon TRIM22 expression induced by IFN-γ. Finally, The TRIM22 nuclear bodies contain also contained CyclinT1, a crucial elongation factor of HIV-1 primary transcripts. These findings show that TRIM22 nuclear bodies are a site of recruitment of factors crucial for the regulation of HIV-1 transcription and highlighting the potential existence of a concerted action between TRIM22, CIITA and TRIM19/PML to maintain a state of proviral latency at least in myeloid cells.